The Development of Comic on Sub-Theme “National Events” Concerning National Dependence Proclamation to Inculcate Discipline Character - Chumi Zahroul F; Imam Muchtar (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
The learning process germane to the national events sub-theme surrounding the proclamation of independence requires a media that is able to become a means of delivering abstract material to be concrete not just images available in textbooks, for which more innovative media is needed, namely learning media in comic form. This study aims to produce learning media in the form of comics that can foster the character of discipline, using the R & D model from Borg and Gall (2003) which consists of 7 stages. It aims to describe the process, produce products and disseminate products. The aspects of media quality studied are validity and effectiveness. The media developed is evaluated by material experts and media to determine its feasibility. The subjects of this study were all VA students of SDN Kebonsari 03 Jember, which included 35 students as subjects of the small-scope trial. 25 VA students from Public Elementary School Kebonsari 04 Jember were involved in a control class, and 26 VB students were involved in the experimental class. The data collection in this study was done through observation, interviews, questionnaires, tests, and validation. The results of data analysis showed that the media was proven valid with the validator percentage validating 80.3%. The percentage of student learning outcomes was 82.35%. The average results of student affective assessment for disciplinary characters are 95%. From these results, it can be concluded that comic media has fulfilled the quality aspects of the media and can be used as a medium of learning in schools. In the field trial, the results obtained for the control class average pretest score was 75.2 and the average posttest score was 82.5. The experimental class obtained an average score of 78.1 in pretest and 90.2 in the posttest score. Learning with comic media developed is proven effective to foster the character of discipline.